Learning to read aligns visual analytical skills with grapheme-phoneme mapping: evidence from illiterates - Lachmann, Thomas; Khera, Gunjan; Srinivasan, Narayanan; Van Leeuwen, Cees (Frontiers in Evolutionary Neuroscience, 2012)
Learning to read puts evolutionary established speech and visual object recognition functions to novel use. This leads to particular rearrangements and differentiations in these functions, for instance the habitual preference for holistic perceptual organization for visual object recognition in contrast with its suppression in recognizing and classifying letters. We performed an experiment in which the differentiation between holistic non-letter processing and analytic letter processing in literates was originally shown (van Leeuwen & Lachmann, 2004) with illiterate adults. The original differentiation is absent in illiterates; they uniformly showed analytic perception for both letters and non-letters. The result implies that analytic visual perception is not a secondary development resulting from learning to read but, rather, a primary mode of perceptual organization that is suppressed for non-letter objects in skilled readers.